(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: High-quality documentation of medical records is necessary to carry out smooth communication between healthcare providers, to provide efficacious patient care, and for legal reasons. However, incomplete or poor documentation is a frequent issue that can affect the safety and care of patients (1). Objective: To evaluate and improve the quality as well as the completeness of inpatient medical record documentation using the Plan-Do-Study-Act (PDSA) cycle in Al Nafees Medical College and Hospital, Islamabad. Methodology: A clinical audit was carried out using the PDSA quality improvement methodology. The standardized history form used by Al Nafees Medical College and Hospital was compared with the standards of the Royal College of Physicians, United Kingdom to evaluate the quality. Following quality evaluation, the completeness of the form was also compared using a standardized checklist following GMC and Royal College of Physicians guidelines. Interventions such as educational sessions, distribution of standardized history templates, and workshops were carried out to improve the documentation practices of junior doctors. A re-audit was conducted post-interventions to measure the changes. Results: The audit revealed that none of the inpatient records were according to the established standards, with common deficiencies in the history section, additional history section, and discharge section. Post-interventions, compliance led to significant improvement in quality and completeness. Conclusion: The PDSA cycle constructively identified and conveyed key issues in inpatient medical record documentation. Interventions led to significant improvements, explaining the importance of continuous improvement in clinical setups.